The determinants of value added tax revenues in the European Union - Sarmento, Joaquim (2017)
In this paper we assess the critical factors of Value Added Tax revenues in the European Union, by using a panel data of the 27 countries, between 1998 and 2011. Our findings show that EU governments have been using tax rates increases to collect more revenues, both at the normal and the minimum rate. It was also found that an increase in the implicit rate increases revenues as well. Tax administration efficiency and experience is a critical factor for the capacity to collect VAT revenues. A better legal and institutional environment is shown to be related with higher revenues. Finally, countries in the Eurozone are shown to have higher revenues, mainly due to the fiscal rules that they are subject to. Higher income, as measured by GDP per capita, increases revenues, on account of the higher propensity for consumption.